TACTILE NAVIGATION: AN ADDITIONAL PROCESSING CHANNEL FOR ENVIRONMENTS OF HIGH SENSORY LOAD - Bharadwaj, Arnav (My University, 2017)
Persons with visual impairments often rely on navigational electronic aids, which typically employ speech commands for guidance through novel routes. However, navigational speech commands may interfere with the perception of acoustically rich environmental information, resulting in potentially detrimental effects. We investigated the sense of touch as a means to convey navigational commands instead. The somatotopic representation of the body surface within the central nervous system makes spatial information intuitive to our skin, suggesting that the tactile channel should be equivalent to, if not better than, the auditory channel at processing directional commands. Additionally, based on Wickens’ Multiple resource theory, the tactile channel should mitigate the sensory load in the auditory channel in travelers with visual impairments. We tested the ability of blind users to process directional commands conveyed via a tactile navigational belt. 14 blind participants were tested with the tactile belt under conditions of either low or high acoustic sensory load, simulating different outdoor environments. For comparison, the same participants were tested also with a conventional auditory device. Consistent with previous studies, we found navigation with the tactile belt to be less efficient than navigation with the auditory aid in the absence of environmental sounds. However, we found also – for the first time, to our knowledge – that tactile performance was less compromised under conditions of high acoustic sensory load. These results will help to inform the further investigation and development of tactile displays to benefit blind travelers.
Keywords: Tactile Navigation; Tactile information; tactile channel; multiple resource theory; audio GPS; sensory load